Improving the use of Agricultural Land in Kashkadarya Region - Ochilova N. A. (Research Parks Publishers, 2022)
This article analyzes the land using of farms and the population of Kashkadarya region, the types of crops grown, their level of productivity, changes in gross yield, the factors influencing their impact on the proposed and analytical factors.